1989
DOI: 10.3354/meps053191
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the food requirements of striped bass larvae Morone saxatilis: effects of light, turbidity and turbulence

Abstract: Laboratory experiments were conducted to study the effects of food concentration, turbulence and turbidity on growth and survival of striped bass larvae Morone saxatilis. Initial experiments indicated that striped bass larvae could forage and grow well ( G = 0.143 to 0.179 d-l) at food concentrations ranging from 50 to 250 ind I-' of the copepod Eurytemora affinis and that growth was similar on Artemia sp. and E. affinis. Subsequent experiments tested effects of turbidity (50, 100, 150 ppm kaolin), reduced lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 19 publications
(19 reference statements)
6
102
0
Order By: Relevance
“…For example, walleye have higher growth rates at higher water temperatures regardless of latitudinal differences among populations (Galarowicz and Wahl, 2003). Other factors include turbidity, which can negatively affect the feeding efficiency of visual predators (Chesney, 1989;Utne-Palm, 2004), as well as primary productivity (inferred from chlorophyll a concentrations), which can affect food availability at higher trophic levels (McQueen et al, 1986). Resource availability can affect lower trophic levels, as increased nutrients from resuspension of sediments (Schindler, 1978) can increase phytoplankton biomass that may lead to increases in zooplankton biomass.…”
Section: Introductionmentioning
confidence: 99%
“…For example, walleye have higher growth rates at higher water temperatures regardless of latitudinal differences among populations (Galarowicz and Wahl, 2003). Other factors include turbidity, which can negatively affect the feeding efficiency of visual predators (Chesney, 1989;Utne-Palm, 2004), as well as primary productivity (inferred from chlorophyll a concentrations), which can affect food availability at higher trophic levels (McQueen et al, 1986). Resource availability can affect lower trophic levels, as increased nutrients from resuspension of sediments (Schindler, 1978) can increase phytoplankton biomass that may lead to increases in zooplankton biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens collected for this study were all taken at night so that survey catchability would be high, whereas most dietary studies that report sampling time occurred during daylight hours. Although Striped Bass larvae do feed at night (Chesney 1989;McHugh and Heidinger 1977), Duston and Astatkie (2012) found that the prey capture rate of larval Striped Bass at night depends on prey densities; visual feeding was up to four-fold more effective than nonvisual feeding at low prey densities but similar at the highest densities. Nonetheless, we found no effect of tow time on gut fullness (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Increased turbidity is more disruptive to animals that detect prey from a long-distance in contrast to those that detect prey at short distances (Chesney 1989;Giske et al 1994;Rowe and Dean 1998). Therefore, turbidity affects animals differently depending on their visual ecology; and those animals that are not predominantly visual may be unaffected by changing turbidity levels, including many invertebrates, which dominate animal biomass in rivers.…”
Section: Turbidity Suspended Sediment and Water Claritymentioning
confidence: 99%